Valuing the past in the Greco-Roman world : proceedings from the Penn-Leiden Colloquia on Ancient Values VII - Ker, James, 1970-; Pieper, Christoph (Mnemosyne, bibliotheca classica Batava. Supplementum. Monographs on Greek and Roman language and literature ;, 2014)
Valuing the Past in the Greco-Roman World is a collaboration between scholars working on diverse areas and periods of ancient Greco-Roman culture. The volume addresses literary and material evidence for ancient notions of valuing (or disvaluing) the deep past.